2020
DOI: 10.1186/s13287-019-1492-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effect of hCMSCs and liraglutide combination in ALI through cAMP/PKAc/β-catenin signaling pathway

Abstract: BackgroundALI/ARDS is the major cause of acute respiratory failure in critically ill patients. As human chorionic villi-derived MSCs (hCMSCs) could attenuate ALI in the airway injury model, and liraglutide, glucagon-like peptide 1 (GLP-1) agonist, possesses anti-inflammatory and proliferation promotion functions, we proposed to probe the potential combinatory effect of hCMSCs and liraglutide on ALI.MethodsWe examined the time- and dose-dependent manner of GLP-1R, SPC, Ang-1, and FGF-10 with LPS via western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Therefore, DPP4 inhibitors could be continued, at least in mild cases of COVID-19, while potential benefit in treating CoV infection remains to be studied further [78]. Similarly, GLP-1RAs are known to have anti-inflammatory effects and have shown potential for therapeutic benefit in acute lung injury [79]. However data are limited to experimental models and their benefit, at best, remains speculative.…”
Section: Specific Therapies For Covid-19 In People With Diabetesmentioning
confidence: 99%
“…Therefore, DPP4 inhibitors could be continued, at least in mild cases of COVID-19, while potential benefit in treating CoV infection remains to be studied further [78]. Similarly, GLP-1RAs are known to have anti-inflammatory effects and have shown potential for therapeutic benefit in acute lung injury [79]. However data are limited to experimental models and their benefit, at best, remains speculative.…”
Section: Specific Therapies For Covid-19 In People With Diabetesmentioning
confidence: 99%
“…In addition, it was reported that liraglutide could treat myocardial infarction by increasing myocardial blood flow, inhibiting cardiomyocyte apoptosis, and enhancing cardiac function [29]. It has also been found in our previous research that liraglutide can be combined with MSCs to alleviate the symptoms of ALI [30].…”
Section: Introductionmentioning
confidence: 71%
“…204656-20-2, China) (LPS + liraglutide group). The concentrations of LPS and liraglutide were selected based on previous studies of MSCs viability [30]. After 6,24,48, and 72 h of incubation, 10 μL of 5 mg/mL MTT (M2128, Sigma, USA) solution was added to each well and continued to culture at 37°C for 4 h. Cells were lysed using 100 μL of dimethylsulfoxide (DMSO, 67-68-5, Sigma, USA).…”
Section: Mtt Assaymentioning
confidence: 99%
“…They are derived from the bone marrow, placental chorionic membrane and the lung respectively. Previous studies have shown that BMSCs, LRMSCs and hCMSCs play protective roles in lung injury caused by mechanical ventilation injury, endotoxin and plateau factors [6,8]. Other studies have reported that BMSCs can improve the lung injury caused by phosgene [4].…”
Section: Discussionmentioning
confidence: 99%
“…LRMSCs can signi cantly improve in ammatory response and reduce pulmonary edema in endotoxininduced lung injury [7]. HCMSCs also play a repair role in lung injury [8]. However, the speci c effects of LRMSCs and hCMSCs in phosgene inhalation lung injury have not been reported.…”
Section: Introductionmentioning
confidence: 99%